Cerdas Bermedia: Panduan Orang Tua dan Anak Memilah Informasi di Tiktok - Nabila Fitriani; Wiam Fadlul Rahman (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to educate both parents and children in sorting information on the TikTok application. The problem that will be described in this study is the lack of digital literacy education which causes a lack of awareness of credibility related to the actual facts, this study uses an analytical descriptive method with literature study techniques, the object of research is the user of the TikTok application. This research has the potential to be a reference for subsequent research.